Perancangan Aplikasi Sistem Akademik Berbasis Web Menggunakan Metode Waterfall: - Rasyiid, Muhammad Raditya; Yusuf, Sukma Maulana; Maulana, Muhammad Teguh; Putra, Rani Laple Satria (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
This research aims to design a web-based academic information system at SMP PGRI 9 Jakarta, with the goal of facilitating academic processes. The delivery of information, such as teacher data, student data, subjects, and classes, currently faces challenges in speed and efficiency, leading to data congestion and requiring a significant amount of time to manage. Therefore, a system is needed to address these issues. This system is designed using the PHP programming language with a MySQL database and applies the waterfall development method. The objective of this research is a web-based academic information system accessible to teachers and school staff, enabling easy access to school information.